2022
DOI: 10.1007/s40865-022-00219-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cohabitation, Marriage, and Suspected Crime: a Longitudinal Within-Individual Study

Abstract: The effects of marriage on criminal behavior have been studied extensively. As marriages today are typically preceded by cohabiting relationships, there is a growing need to clarify how different relationship types are associated with criminality, and how these effects may be modified by relationship duration, partner’s criminality, and crime type. We used Finnish longitudinal register data and between- and within-individual analyses to examine how cohabitation and marriage were associated with suspected crime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Marriage has been extensively discussed in the desistance literature, and in the Nordic context research has shifted towards emphasizing cohabitation (Airaksinen et al 2023;Jalovaara 2013;Skardhamar et al 2015). As for living in housing, in this study, the period-wise context was only negligibly associated with marriage probabilities, but cohort coefficients exhibited a falling trend.…”
Section: Contextmentioning
confidence: 72%
See 1 more Smart Citation
“…Marriage has been extensively discussed in the desistance literature, and in the Nordic context research has shifted towards emphasizing cohabitation (Airaksinen et al 2023;Jalovaara 2013;Skardhamar et al 2015). As for living in housing, in this study, the period-wise context was only negligibly associated with marriage probabilities, but cohort coefficients exhibited a falling trend.…”
Section: Contextmentioning
confidence: 72%
“…However, more recent studies in the Scandinavian context have disputed this claim and in turn suggest that marriage is merely an end point of the desistance process and that identity transformation and crime reduction already occur before marriage (Lyngstad and Skardhamar 2013;Skardhamar et al 2015) reflecting changes in gender roles. Moreover, Finnish studies have found that cohabitation is associated with greater reductions in offending than is marriage (Airaksinen et al 2023;Savolainen 2009). Beyond this study, the trends of marriage and cohabitation among individuals involved in the Finnish criminal justice system are unknown.…”
Section: Marriage and Cohabitationmentioning
confidence: 77%